Modulating the phase transition between metallic and semiconducting single-layer MoS2 and WS2 through size effects. Issue 2 (21st November 2014) - Hu, Ziyu; Zhang, Shengli; Zhang, Yan-Ning; Wang, Da; Zeng, Haibo; Liu, Li-Min
Abstract : The first-principles calculations are performed to investigate the electronic properties and atomic mechanism of the single layer MoS2 or WS2 homo-junction structure. Abstract : The first-principles calculations are performed to investigate the electronic properties and the atomic mechanism of the single layer MoS2 or WS2 homo-junction structure. The results reveal that both the stability and electronic structure of the homo-junction structure are greatly affected by the type of boundaries, which connect the different phase structures, either the semiconducting hexagonal (H) structure or the metallic trigonal (T) structure. Through tuning the size of the lateral homo-junction structure of either MoS2 or WS2, the phase transformation between H and T can occur. Interestingly, the electronic structures of homo-junction structures can be tuned between the metal and the semiconductor by changing the size of the nanoribbons.